Open Reduction, Bone Grafting, and Internal Fixation of Osteochondritis Dissecans Lesion of the Knee - Herring, Matthew J. (JBJS Essent Surg Tech, 2019)
Osteochondritis dissecans (OCD) of the femoral condyle is an idiopathic focal bone abnormality affecting the subchondral bone and can result in unstable osteochondral lesions. The treatment of unstable OCD lesions with open reduction and internal fixation with metallic compression screws is well documented in the literature. Fixation is performed to prevent dislodgement of unstable OCD lesions or fix displaced fragments that have been surgically reduced. The procedure is performed by approaching the knee through a midline incision and medial parapatellar arthrotomy. The lesion is identified, and a scalpel is used to incise the cartilage circumferentially, leaving 1 side intact, to create a “trap door” flap. The OCD fragment is lifted from the bed, and the bed is prepared by debriding the fibrocartilage scar and bone-grafting the bed. The osteochondral fragment is reduced back to the bed, and guidewires are placed to secure the reduction and plan screw trajectories. Guide pins are overdrilled and Herbert compression screws are placed to secure the OCD fragment. The wound is irrigated and closed. Complications are rare, but later screw removal is typically recommended. Reported outcomes are satisfactory, with an 80% rate of radiographic healing and good-to-excellent patient-reported outcomes.